Segregation over time in functional networks in prefrontal cortex for individuals suffering from pathological fatigue after traumatic brain injury - Skau, Simon; Johansson, Birgitta; Kuhn, Hans-Georg; Thompson, William Hedley (Frontiers in Neuroscience, 2022)
Pathological fatigue is present when the trait fatigue is perceived to interfere with everyday life. Pathological fatigue has been linked with a dysfunction in the cortico-striatal-thalamic circuits, and previous studies have investigated modularity and other measures for segregation using functional connectivity, with results showing both increase and decrease in segregation. Studies does also vary depending on if the analysis is done during rest or during a task. Questions that need to be further explored relating to network theory and fatigue are: i) are the brain networks of patients with pathological fatigue display more segregation or integration compared to healthy controls? ii) Do network properties differ depending on whether patients with pathological fatigue perform a task compared to periods of rest? ii) Are the brain networks of patients with pathological fatigue and healthy control differently affected by prolonged cognitive activity? We recruited individual suffering from pathological fatigue after mild traumatic brain injury (n = 20), and age-matched healthy controls (n = 20), to do cognitive activity for 2.5 hour. We used functional near-infrared spectroscopy (fNIRS) to assess hemodynamic changes in the frontal cortex. The participants did a resting state session before and after the experiment, as well as the processing speed test Digit Symbol Coding in the beginning and at the end of the experiment. We conducted an exploratory network analysis on these resting state sessions and Digit Symbol Coding sessions with no a priori hypothesis relating to how patients and controls differ in their functional networks considering previous research have found results in both directions. The result showed a Group vs. Time interaction (p=0.026 ηp²=0.137), with post hoc test reveling that the TBI increased in modularity after the experiment. Together this work helps identify how network analyses of pathological fatigue differ from healthy controls and dynamically change over time as the patient performs tasks over a time scale that affect their fatigue.